Pengenalan Sistem Informasi Pendataan Terpadu Kebutuhan Penyandang Disabilitas di Kabupaten Magetan - Alamsurya Kubara Endriharto; Joko Suprianto (Puslitbang Akademi Relawan TIK Indonesia (ARTIKA), 2023)
Persons with disabilities are part of society who have the same rights and obligations and roles as other members of society. Data collection for disturbances must be carried out properly so that this makes the Magetan ICT Volunteers and the Magetan Regency Social Service must have a good database system. This paper aims to provide a website design for stakeholders on data problems in Magetan Regency. The method used in designing this system is observation, data collection and information needed in designing the system. The result is to produce an Integrated Data Collection Information System for the Needs of Persons with Disabilities, abbreviated as SI PERKASA. This system can provide complete and accurate information according to the criteria, through services for inputting data to the admin and being able to provide it in the form of tables and graphs.